Pengembangan Perangkat Pembelajaran Kimia SMA Berbasis Predict-Observe-Explain pada Materi Larutan Asam Basa - Basir, Nur Eka Sari; Danial, Muhammad; Husain, Halimah (Chemistry Education Review (CER), 2020)
This study is a development research that aims to produce high school chemistry learning device based on Predict-Observe-Explain on acid-base solution material which has valid, practical, and effective criteria. The development model used in this study refers to the 4D development model, which consists of the defining stage, design stage, development stage, and the dissemination stage. The learning device developed are RPP, LKPD, BPD, and THB. Two experts validated the Chemistry learning device based on Predict-Observe-Explain developed. After being validated, a Predict-Observe-Explain-based learning device was tested at SMA Negeri 11 Makassar in class XI MIA 4 with 35 students. The results of this study indicate that the Predict-Observe-Explain-based learning tools developed had been through a validation process, measuring the level of practicality and effectiveness. The learning device is stated as valid based on: (1) the result of RPP validation with a value of 3.7, (2) the result of the LKPD validation with a value of 3.8, (3) the result of BPD validation with a value of 3.8, and (4) the THB validation result with a value of 3.8. The learning device is stated as practical based on: (1) the implementation of the Predict-Observe-Explain-based learning device is at an average value = 1.96, (2) the teacher gave a very positive response to the learning device with a percentage of 91.04%, and (3) students gave a very positive response to the learning device with a percentage of 89.96%. The learning device is stated as effective based on: (1) the learning outcomes obtained an classical completeness 85.71% with a high category, and (2) the students’ learning motivation obtained an average percentage of 81.77% with the category of completion. Therefore, the results of the study show that Predict-Observe-Explain based learning device products have valid, practical, and effective qualities.